Functional nanofibers in clothing for protection against chemical and biological hazards - Nurfaizey , Abdul Hamid; Tucker, Nick; Stanger, Jonathan; Staiger, Mark (Woodhead Publishing, 2012)
Functional nanofibers have great potential to improve protection against chemical and biological warfare agents. This chapter reviews the history of chemical and biological warfare and existing protective technologies. The use of electrospinning to produce nanofibers for protective applications is also introduced. Previous studies demonstrate the applicability of electrospun nanofibers in protective fabric technologies. Advantages of these next-generation protective materials include high penetration resistance, excellent breathability, low basis weight, low pressure drop, the potential for the incorporation of surface chemical functionality and simple processing equipment. Finally, the main development issues and potential research directions of electrospun nanofibers in protective applications are discussed.